2021
DOI: 10.7554/elife.63762
|View full text |Cite
|
Sign up to set email alerts
|

Glycine acylation and trafficking of a new class of bacterial lipoprotein by a composite secretion system

Abstract: Protein acylation is critical for many cellular functions across all domains of life. In bacteria, lipoproteins have important roles in virulence and are targets for the development of antimicrobials and vaccines. Bacterial lipoproteins are secreted from the cytosol via the Sec pathway and acylated on an N-terminal cysteine residue through the action of three enzymes. In Gram-negative bacteria, the Lol pathway transports lipoproteins to the outer membrane. Here we demonstrate that the Aat secretion system is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…This effect is specific to the Rns-dependent pilins because the expression of flagellin and other proteins of unknown identity was largely unaffected by the addition of decanoic acid. Likewise Rns-dependent expression of the outer membrane lipoproteins CexEα and CexEε 54 , 55 was inhibited by decanoic acid in a dose dependent manner (Fig. 4 a).…”
Section: Resultsmentioning
confidence: 80%
“…This effect is specific to the Rns-dependent pilins because the expression of flagellin and other proteins of unknown identity was largely unaffected by the addition of decanoic acid. Likewise Rns-dependent expression of the outer membrane lipoproteins CexEα and CexEε 54 , 55 was inhibited by decanoic acid in a dose dependent manner (Fig. 4 a).…”
Section: Resultsmentioning
confidence: 80%
“…For whatever reason Lit came to exist, it has the advantage over Lnt and the recently discovered LnsAB 38 and AatD 39 , 40 , the only other known amino terminus acylating enzymes, that upon reaction it does not produce a lyso-phospholipid (lyso-PL) as a second product 1 . Lyso-PLs, as the name implies, are potent surfactants that, at high enough concentrations, will effectively punch holes in and eventually solubilise membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein interactions with receptors, TLR2/1 and TLR2/6, are indicated in c – e . A different type of lipoprotein, where processing involves signal peptidase I cleavage and acylation at an N-terminal glycine, has been described recently 39 , 40 . …”
Section: Introductionmentioning
confidence: 99%
“…Recent data have shown that N-terminal glycine monoacylation by palmitate (C16) of the CexE lipoprotein is ensured by the AatD subunit of the Aat secretion system [328,329]. AatD is a close relative of Lnt, part of the nitrilase family.…”
Section: Glycine Acyltransferases In Bacteriamentioning
confidence: 99%